sj-docx-1-cjk-10.1177_20543581221150676 – Supplemental material for Development and Validation of Patient Education Tools for Deprescribing in Patients on Hemodialysis - Thomas Hyunwoo Cho; Patrick C. K. Ng; Melissa J. Lefebvre; Arlene Desjarlais; Dennis McCann; Blair Waldvogel; Marcello Tonelli; Amit X. Garg; JoAnne Wilson; Monica Beaulieu; Judith Marin; Cali Orsulak; et al. (SAGE Journals, 2023)
Supplemental material, sj-docx-1-cjk-10.1177_20543581221150676 for Development and Validation of Patient Education Tools for Deprescribing in Patients on Hemodialysis by Thomas Hyunwoo Cho, Patrick C. K. Ng, Melissa J. Lefebvre, Arlene Desjarlais, Dennis McCann, Blair Waldvogel, Marcello Tonelli, Amit X. Garg, JoAnne Wilson, Monica Beaulieu, Judith Marin, Cali Orsulak, Melanie Talson, Monica Sharma, Jordanne Feldberg, Clara Bohm and Marisa Battistella in Canadian Journal of Kidney Health and Disease
Keywords: Medicine